Increase in the piezoelectric response of scandium-doped gallium nitride thin films sputtered using a metal interlayer for piezo MEMS - Uehara, Masato; Mizuno, Takaaki; Aida, Yasuhiro; Yamada, Hiroshi; Umeda, Keiichi; Akiyama, Morito (Applied physics letters, 2019)
Wurtzite gallium nitride (GaN) has a polarity along the c-axis and piezoelectric properties the same as aluminum nitride. Since it has a high mechanical quality factor and high output sensitivity, it is expected to perform well in piezo micro-electro-mechanical system devices. This paper demonstrates that Hf and Mo interlayers enable the preparation of highly (001)-oriented GaN films via conventional sputtering at a low temperature (400 °C). The piezoelectric coefficient d33 of the prepared undoped GaN films is equivalent to that of a single-crystal GaN. Furthermore, the results demonstrate that the piezoelectric response of GaN films increases significantly when they are doped with scandium (Sc). Although this enhancement was predicted theoretically, the piezoelectric response of Sc-doped GaN films prepared on Hf and Mo interlayers has shown great improvement. Moreover, bulk acoustic wave resonators constructed using Sc-doped GaN films show a piezoelectric coupling factor that is three times larger than that of a single-crystal GaN.